2015
DOI: 10.1093/heapro/dav021
|View full text |Cite
|
Sign up to set email alerts
|

Health promoting interactive technology: Finnish, Norwegian, Russian and Swedish students' reflections

Abstract: The aim of this study was to elucidate Finnish, Norwegian, Russian and Swedish students' reflections and ideas on how interactive technology can be used to promote health in school. The data were collected in the northern part of these four countries, and 630 students aged 13-15 filled out the World Health Organization's 'Health Behavior in School-Aged Children' self-completion questionnaire with one additional open question, which is analyzed in this article (n = 419). The phenomenological analysis resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Girls' well-being was promoted by having good social relationships with family and friends and this is congruent with findings in previous studies (Derdikman-Eiron et al, 2011;Spein et al, 2013;Camara et al, 2014). In addition, our results agree with findings from Kostenius and Hertting's (2015) study where they state that good relationships increase well-being. Ahonen (Ahonen, 2006) found in his study, that girls generally had less social contact than boys and in Finland the pupils had the least friends compared to Sweden, Russia and Norway.…”
Section: Discussionsupporting
confidence: 93%
“…Girls' well-being was promoted by having good social relationships with family and friends and this is congruent with findings in previous studies (Derdikman-Eiron et al, 2011;Spein et al, 2013;Camara et al, 2014). In addition, our results agree with findings from Kostenius and Hertting's (2015) study where they state that good relationships increase well-being. Ahonen (Ahonen, 2006) found in his study, that girls generally had less social contact than boys and in Finland the pupils had the least friends compared to Sweden, Russia and Norway.…”
Section: Discussionsupporting
confidence: 93%
“…He points out that being a digital native means growing up in the digital culture and this might be the situation in the case of the children in this study taking technology for granted. Whatever the case may be we can conclude that schoolchildren in other studies point out that interactive technology not only promotes empowerment and independence but offer a way to socialize with friends, providing a tool to create good relationships which increase well-being (Kostenius and Hertting, 2015). Although the schoolchildren in this study did not mention technology the friendship aspect was found throughout the theme “Appreciation as fuel for health and well-being.”…”
Section: Discussionmentioning
confidence: 94%
“…This can be argued for as Maria having the power to remove herself from a situation in which she was not comfortable, increasing autonomy. Similarly, Kostenius and Hertting ( 2016 ) conclude that students express that interactive technology gives them a sense of control. They go on explaining that meeting and learning online, or in a virtual space, offer students opportunities to take responsibility and exercise self-control.…”
Section: Philosophical Explorations Of Interpersonal Relationships Inmentioning
confidence: 97%
“…Others have also argued for the opportunities of online communication as they found that it enhances self-esteem, relationship forming, friendships, and increases friendship quality (Valkenburg & Peter, 2011 ). According to students, the use of interactive technology in school promotes good relationships as it offers a way to socialize, provides a tool for meeting, and gives support when encouraging classmates (Kostenius & Hertting, 2016 ). Also, students’ experiences of health and wellbeing in the school context point to the importance of being cared for, confirmed by and connected to others (Kostenius et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation